Developments in the disclosure standards of Singapore in the economy. - Tan, Ernie. (2008)
This paper discusses recent developments of disclosure practices in Singapore. Based on a previous study, research was also done to assess the time taken by a sample of 465 Singapore listed companies to report their annual results.